Upper respiratory tract infection in children – immunostimulating treatment - Kaczmarczyk, Dariusz; Zagacki, Dawid; Morawiec-Sztandera, Alina (Journal of Education, Health and Sport, 2021)
This paper is a review of publications on viral infections of the upper aerotract in children. Recurring infections can be a consequence of the lack of treatment, inappropriate therapy or accompanying diseases. It is possible that an impaired condition of immunity leads to recurring infections. In this review a great deal of attention has been given to the mechanisms and the various stages of viral infection, and the onset of an organism’s defense mechanisms against viruses. The function of the immunomodulatory and immunostimulatory medical product, namely inosine pranobex has been evaluated in in vitro and in vivo studies. A review of the antiviral activity of inosine pranobex and the onset of cellular and humoral immunity has been presented.